PERANCANGAN BISNIS DAN IMPLEMENTASI PAKETEMPAT: APLIKASI PENYEWAAN RUANGAN - Previana, Cantika Nur; Andhika, Andhika; Maulansyah, Muhamad Rizky; Prasetyo Pribadi, Arga Seno (Politeknik META Industri Cikarang, 2023)
An activity such as office meetings, gatherings, and business needs are often conducted outside the office premises. Various locations commonly used include halls, private meeting rooms, cafes, or other paid public spaces. However, booking these places can be time-consuming and costly. To address this issue, there is a need for an online platform that connects space owners and renters. Paketempat serves as an online platform where individuals, communities, organizations, or groups can find suitable locations for gatherings, meetings, or office purposes, with a different atmosphere and budget to match their needs (in the Malang and surrounding areas). The goal is for both renters and space owners to benefit from this platform. Renters can discover new environments for their events, find places that align with their theme and budget, and save time. Space owners can profit financially by utilizing and renting out their available spaces by the hour or day. From this application, several usability responses have been gathered from both owners and users of Paketempat. In general, the survey results, conducted through a Google form distributed to Paketempat users, have been positive, encompassing speed, completeness of information, and user interface.